Vocational Educators’ Job Satisfaction and Value Creation: Antidotes for their Job Retention - Owenvbiugie, Robinson Osarumwense; Abusomwan, Sunday Bello (NIU Journal of Social Sciences, 2020)
The study assessed how vocational educators’ job satisfaction and value creation serve as antidotes for their job retention in tertiary educational institutions in Edo and Delta States. Variables such as tenure, salary, excellent compensation and training and development were assessed. Four research queries were provided answers to. Two reasonable guesses were tested. Descriptive survey research was applied. 329 vocational educators were used for the study. A total of 318 questionnaires were found usable representing 96.7 percent. The instrument was validated by Three experts validated the items in the questionnaire. The instrument yielded 0.88 using the Cronbach alpha to enhance its face and content validity. The descriptive statistics was used to answer all questions raised for the study. The hypotheses were tested with the t-test statistics.  Vocational Educators’ Job Satisfaction and Value Creation Questionnaire (VEJSVCQ) were administered on the respondents by the researcher with two supporting persons. Results revealed vocational educators: male and female, married and single, were satisfied with job tenure, salary they earned. It also revealed vocational educators were satisfied with excellent compensation, training and development. Male vocational educators do not differ from female vocational educators in their levels of job satisfaction. Married vocational educators do not differ from single vocational educators in their levels of job satisfaction. The study recommended that vocational educators’ job satisfaction may be improved if management and councils of various tertiary institutions pay necessary attention to staff welfare in terms of regular review of salary paid to staff, and security of workers’ job. Keywords: Job satisfaction; Value creation; Job retention; Salary; Job tenure; Excellent Compensation; Training and development